Características morfométricas de seis clones de café con la aplicación de abonos orgánicos. - Brito Chango, Manuel Ricardo (2020)
The research work was carried out at the Sacha Wiwa Experimental Center, belonging to the SEIC Foundation, Canton La Maná. The objectives were: to analyze the growth indicators in coffee plants with the application of humus fertilizers and slaughterhouse waste. To determine the clones that best result with the application of organic fertilizers in coffee plants. To perform a comparative analysis between clones and fertilizers to determine the most outstanding treatments in coffee cultivation. A Random Block Design was used, with three treatments and three repetitions, a 2x6 factorial arrangement was applied, with Factor A: Coffee Clones and Factor B: Fertilizers. The results were: higher plant height with clone EET 3756-14 applied humus, with 48.72 cm, at 60 days the highest plant height was obtained with clone NP-2024 which obtained 56.89 cm. with slaughterhouse waste and 55.94 cm. With the humus, height of 90 days was given with the NP3056 with 60.84 cm height, at 120 days the result with the highest height was for the NP2040 with 69.31 centimeters. As for the stem diameter, the greatest result at 30, 60 and 90 days was obtained with COF01 and humus with 1.29 and 1.37 1.48 centimeters respectively, at 120 days the largest stem diameter was obtained with the NP2024 with 1.62 centimeters. For the variable leaf perimeter index, the highest results were obtained with clone NP2024 and humus fertilizer with 73.17, 76.00, 78.72 and 83.34 centimeters, at 30, 60, 90 and 120 days respectively.